An analysis of operational efficiency and its influencing factors in traditional Chinese medicine hospitals in Shaanxi Province, China - Zhang, Jieming; Li, Yan; Qu, Huiyang; Chen, Penggang (Frontiers in Public Health, 2025)
BackgroundOver the past decade, traditional Chinese medicine (TCM) hospitals in China have experienced significant growth. However, their developmental status remains unclear, posing challenges to the formulation and optimization of relevant healthcare policies. This study aimed to assess the operational efficiency of TCM hospitals in Shaanxi Province and explore its influencing factors, thereby providing empirical evidence to support performance improvement.MethodsA total of 167 TCM hospitals in Shaanxi Province were included in this study. The Bootstrap Data Envelopment Analysis (Bootstrap-DEA) was utilized to calculate bias-corrected operational efficiency scores. Subsequently, Tobit regression analysis was used to identify significant determinants of efficiency, offering a comprehensive understanding of influencing factors.ResultsAfter bias-correction, operational efficiency scores decreased across all hospitals. Tertiary hospitals had the highest mean operational efficiency score (0.457), followed by secondary hospitals (0.374), unclassified hospitals (0.354), and primary hospitals (0.329). Tobit regression indicated that the total number of visits, number of discharged patients, and bed occupancy rate positively influenced efficiency scores (p < 0.05), whereas number of employees and average length of stay had a negative impact (p < 0.05).ConclusionThe development of TCM hospitals in Shaanxi Province remains uneven, and overall operational efficiency is suboptimal. Enhancing efficiency requires targeted strategies, such as optimizing staffing levels, reducing the average length of stay, and improving bed utilization. These findings offer practical insights for policymakers to support the sustainable development of TCM hospitals.